Comprehensive analysis of causal pathogens and determinants influencing black rot disease development in MD2 pineapples - Kuruppu, Manori; Siddiqui, Yasmeen; Khalil, Hala Badr (Frontiers in Microbiology, 2025)
Malaysia ranks among the world’s top 20 pineapple producers, driven by the success of the MD2 variety in meeting domestic and international demand. However, postharvest losses due to pathological diseases remain a challenge. Black rot, a major postharvest disease, causes significant economic losses in pineapples. Despite its presence in various cultivars, its aetiology, specifically in MD2 pineapples remains unclear. This study was conducted to identify the principal causative pathogen of black rot disease in pineapple from three different regions. In addition, critical factors influencing black rot disease were investigated, such as the minimum inoculum concentration, appropriate storage temperature, and maturity index required to initiate infection. Thielaviopsis paradoxa was identified as the primary pathogen causing black rot, with 50 and 45% occurrence at two specific cultivation sites. Other associated pathogens included Lasiodiplodea theobromae, Trichoderma asperellum, Curvularia eragrostidis, Neoscytalidium dimidiatum, Aspergillus assiutensis, and Aspergillus aculeatus. Fruits stored at ambient temperature with a maturity index of 2 showed higher disease progression than those in cold storage. A minimum inoculum concentration of 1 × 104 CFU/mL was sufficient for infection at both storage conditions. The Pearson correlation analysis revealed a weak positive link (r > 0.39, p < 0.0001) between harvesting index and fruit pH, while pH and storage temperature had a strong positive correlation (r = 0.83, p < 0.0001). The increments in pH correlated with lesion length and infected area (r = 0.83 and r = 0.82, respectively). The harvesting index showed a strong positive correlation with the proportion of infected area (r = 0.86, p < 0.0001). The telomorph state of T. paradoxa, identified as Ceratocystis paradoxa, persists in soil and decaying plant material, acting as a quiescent pathogen, increasing cross-contamination risks. Urgent measures are required to reduce postharvest losses and maintain the quality of pineapples for international markets.